Analysis of Loss Ratio and Determinants of High Health Insurance Claims in Employee Benefit Programs: A Case Study of PT XYZ for the 2024–2025 Period - Senintyas Frestinawati; Poltak Robert Budhialon; Yulia Indah Permata Sari (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The rising global healthcare costs have placed significant pressure on the sustainability of employer-sponsored health insurance programs. This study aims to analyze the loss ratio and identify the main determinants of high health insurance claims in the employee benefit program of PT XYZ for the 2024–2025 period. The research employed an analytical observational design using secondary claims data from 2024–2025. The analysis was conducted descriptively and inferentially by calculating the loss ratio, examining the frequency distribution of claims, determining the average cost per case, and performing comparative analysis based on type of service and membership status. The results show a loss ratio of 115.37%, indicating an underwriting deficit. Outpatient services dominated claim frequency (±78%), while inpatient services contributed the highest cost per episode. Dependent participants accounted for more than two-thirds of total claims. The primary determinants of increasing claims include the high frequency of outpatient visits, the high cost of inpatient care, and the utilization pattern among dependents. These findings highlight the importance of benefit design evaluation, utilization control strategies, and strengthening promotive and preventive programs to maintain the financial sustainability of the program.